Students' Mathematical Problem Abilities Improvement Using Blended Learning Reviewed From The Initial Ability of Students - Rahmi Ramadhani; Siti Aisyah (UMSU, 2020)
The purpose of this study is to see an increase in students' mathematical problem-solving abilities taught by using a blended learning model in terms of the initial ability of high school students. Blended learning is digital-based learning by using digital learning media as aids in learning. This learning is done as a form of implementation of Education 4.0-based learning which the impact of the existence of Industrial Revolution 4.0. This research uses a quasi-experimental type with a pre-test post-test control design research design. The sampling technique was carried out using purposive sampling and obtained as many as 28 students who were in the experimental group (who were taught using a blended learning model) and 25 students who were in the control group (who were taught using ordinary learning). The results of testing normality and homogeneity of data using Levenes' test and Kolmogorov-Smirnov analysis obtained the results that the data in both learning groups were normally distributed and homogeneous. Referring to the prerequisite test results, hypothesis testing is performed using a Two-Way Analysis of Variance (ANOVA Two Path). The results of hypothesis testing indicate that there is an increase in students 'mathematical problem-solving abilities that are taught using blended learning models in terms of students' initial mathematical abilities. This result strengthens the evidence that the use of blended learning models has a significant effect on improving students' mathematical abilities and provides new learning experiences for students.